Shifting perceptions of intra-party democracy: Leader selection in the Swedish Liberal Party - Aylott, Nicholas; Bolin, Niklas (Frontiers in Political Science, 2023)
The Swedish Liberal Party chose a new leader in 2019. It was, in some ways, typical of leader selection in Sweden. It featured an elaborate, institutionalised and yet only semi-public form of “precursory delegation,” in which aspiring leaders are filtered by a “steering agent” on behalf of the party's main power centres. In other ways, though, the process was unusually conflictual and produced an unexpected result, which had considerable consequences for the party and for Swedish politics. Moreover, the selection involved the breakdown of a long-established procedure for leader selection in the party. We seek to explain this deviant case. We emphasise an unexpected cascade of decisions by regional party branches to hold membership ballots on the leadership candidates. This event, we argue, was critical for the outcome. We also suggest a causal mechanism, a shifting perception of procedural legitimacy, that facilitated the outcome—a mechanism that could be useful in understanding leader selection and moments of party change more generally.